Airlines within airlines: an analysis of US network airline responses to low cost carriers. - Morrell, Peter (Elsevier, 2005)
The establishment of Low Cost Carrier offshoots by network carriers has three possible objectives: to spin off profitable businesses; to see off low cost competition in key markets; and to establish a test-bed for adapting low cost business processes to their mainline operations. It is argued that US network carrier offshoots have failed on all three counts. The significant cost differences between network and Low Cost Carriers are identified, and it is shown that network carriers have made little inroads into closing this gap, whether or not they set up Low Cost Carrier offshoots. Some reasons for the failure of the offshoots are proposed by examining operating differences: mixed fleets, keeping interlining and two class cabins and the lack of progress on reducing labour costs. Labour Union restrictions and the lack of separation from the main airline were crucial.
Ninth Conference of the Air Transport Research Society: Analysis of low cost airlines. July 2004, Istanbul, Turkey
Keywords: Responses to low cost airlines; Productivity; Airline costs